2018
DOI: 10.1111/acel.12710
|View full text |Cite
|
Sign up to set email alerts
|

HTRA1, an age‐related macular degeneration protease, processes extracellular matrix proteins EFEMP1 and TSP1

Abstract: SummaryHigh‐temperature requirement protein A1 (HTRA1) is a serine protease secreted by a number of tissues including retinal pigment epithelium (RPE). A promoter variant of the gene encoding HTRA1 is part of a mutant allele that causes increased HTRA1 expression and contributed to age‐related macular degeneration (AMD) in genomewide association studies. AMD is characterized by pathological development of drusen, extracellular deposits of proteins and lipids on the basal side of RPE. The molecular pathogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 27 publications
2
61
0
Order By: Relevance
“…Thus, the higher RGR expression in the foveal MGs might meet the high demand of cone visual pigment regeneration in the cone-dominated fovea. Additionally, HTRA1, a risk factor gene of AMD, exhibited high expression in the fovea MGs, consistent with the fovea being more vulnerable in AMD [37,38]. Together, our results indicated that MGs in the fovea, as a type of supporting glial cell, expressed specific genes for facilitating cone photoreceptor regeneration, specification, and functional maintenance.…”
Section: Regionally Different Transcriptomes Of Primate Mgs and Conessupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, the higher RGR expression in the foveal MGs might meet the high demand of cone visual pigment regeneration in the cone-dominated fovea. Additionally, HTRA1, a risk factor gene of AMD, exhibited high expression in the fovea MGs, consistent with the fovea being more vulnerable in AMD [37,38]. Together, our results indicated that MGs in the fovea, as a type of supporting glial cell, expressed specific genes for facilitating cone photoreceptor regeneration, specification, and functional maintenance.…”
Section: Regionally Different Transcriptomes Of Primate Mgs and Conessupporting
confidence: 79%
“…We collected single-cell transcriptomic profiles of 119,520 cells, including 38,558 from six healthy human samples (one 8-day old infant and, five adults aged between 35 and 87 years old) and 80,962 from five macaque samples (one 2-year old juvenile and four adults aged between 4 and 23 years old) ( Supplementary Table 1), which covered progressive retinal aging, using dropletbased scRNA-seq (10x Genomics platform). Retinae were dissociated from 1.5-2.0 mm and 5 mm diameter pieces around the center of the foveal pit to represent foveal and peripheral cells, respectively ( Fig.…”
Section: Single-cell Transcriptomes Of Primate Retinamentioning
confidence: 99%
“…Recent studies show that a promoter variant causing increased expression of HTRA1 in RPE cells leads to elevated levels of ECM proteins including HTRA1 substrates (Lin et al, ). Specifically, the HTRA1 substrates vitronectin, clusterin, Adam9, C3, and tubulin were also detected in the human RPE secretome (An et al, ; Melo et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, HtrA1 has been suggested to play a critical role in angiogenesis via TGF-β signalling [37]. Recently, HtrA1 was reported to processes extracellular matrix proteins such as thrombospondin 1 in inducing AMD [38]. It is likely that these HtrA1 actions contribute to the disruption of endothelial tube formation, future studies are warranted to investigate the molecular mechanisms of HtrA1 action in inducing endothelial dysfunction, which will provide important insights into the understanding of how elevated levels of HtrA1 contribute to AMD and earlyonset PE.…”
Section: Resultsmentioning
confidence: 99%